The Role of Local Wisdom in Building Social Resilience Amidst the Global Crisis: A Literature Review of Socio-Cultural Approaches in Indonesia - Ika Rahma (Archipel: Journal of Indonesian Interdisciplinary Studies, 2025)
This study explores the role of local wisdom in building social resilience in Indonesia through a socio-cultural approach, focusing on community adaptation to the global crisis. Using a qualitative research method based on a literature review, this study identifies, analyzes, and synthesizes findings from scientific journals, books, and academic articles related to local wisdom, social capital, and community resilience. Thematic analysis emphasizes that local values such as mutual cooperation, deliberation and consensus, and communal solidarity strengthen social networks, shape collective identity, and facilitate the adaptive capacity of communities in facing external pressures, including pandemics, climate change, and socio-economic disruptions. The findings also indicate that modernization and globalization pose challenges and opportunities for the transformation of local values to remain relevant as adaptive strategies. Based on the literature synthesis, this study proposes an integrative conceptual framework that systematically links local wisdom values, social mechanisms, and social resilience outcomes. This study fills a gap in the literature, particularly the lack of conceptual models linking local culture to social resilience in a global and modernizing context. The research results provide theoretical implications for expanding the study of social resilience as well as practical recommendations for the development of sustainable local culture-based community policies and programs